2013
DOI: 10.1021/bi401022b
|View full text |Cite
|
Sign up to set email alerts
|

A Noncompetitive Inhibitor forMycobacterium tuberculosis’s Class IIa Fructose 1,6-Bisphosphate Aldolase

Abstract: Class II fructose 1,6-bisphosphate aldolase (FBA) is an enzyme critical for bacterial, fungal, and protozoan glycolysis/gluconeogenesis. Importantly, humans lack this type of aldolase, having instead a class I FBA that is structurally and mechanistically distinct from class II FBAs. As such, class II FBA is considered a putative pharmacological target for the development of novel antibiotics against pathogenic bacteria such as Mycobacterium tuberculosis, the causative agent for tuberculosis (TB). To date, seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 57 publications
3
66
0
1
Order By: Relevance
“…S1D in the supplemental material). HCA was previously reported to inhibit the zinc-dependent fructose 1,6-bisphosphate aldolase of M. tuberculosis in enzymatic assays (9,46). In accordance with previous reports (9), we confirmed that the compound is a relatively poor inhibitor of whole cells (see Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…S1D in the supplemental material). HCA was previously reported to inhibit the zinc-dependent fructose 1,6-bisphosphate aldolase of M. tuberculosis in enzymatic assays (9,46). In accordance with previous reports (9), we confirmed that the compound is a relatively poor inhibitor of whole cells (see Fig.…”
Section: Resultssupporting
confidence: 93%
“…2C). HCA displayed no detectable metal-related activity on whole cells over the concentration range tested, despite being previously shown to inhibit Zn-dependent enzymes (50% inhibitory concentration, 10 M) (9).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations